Application of CLIL technology in teaching science subjects in general education schools of Kazakhstan: a survey of teachers (Journal of Educational Sciences, 2020)
Today in the world there are more than seven thousand different languages. In international circles,business, science and other fields of activity, English prevails as the main language of communication. Inthe era of globalization of the world, Kazakhstan is actively implementing a program to modernize theeducation system, the aim of which is to switch to a trilingual education system in secondary schools.Currently, CLIL learning technology is gaining popularity around the world as a new curriculum forlearning an additional language. According to the studies, the use of CLIL technology in the classroomimproves the educational environment of the class, shortens the learning time and, moreover, makes theteaching concept wider and deeper. Despite all its advantages, CLIL can be difficult in some respects. Inview of the complexity of this topic, it is important to have an idea of how effectively the implementationof CLIL training technology in Kazakhstan is taking place. This article presents the results of a survey of127 teachers about the experience of implementing CLIL technology in secondary schools in Kazakhstan.The survey was conducted on social networks for teachers through Whatsapp and Telegram applicationsbased on the Google Forms platform.Key words: CLIL technology, education, trilingualism, modernization.